# Fill in the blanks:

Question:

Fill in the blanks:

(i) $\frac{-23}{17} \times \frac{18}{35}=\frac{18}{35} \times(\ldots . .)$

(ii) $-38 \times \frac{-7}{19}=\frac{-7}{19} \times(\ldots . .)$

(iii) $\left(\frac{15}{7} \times \frac{-21}{10}\right) \times \frac{-5}{6}=(\ldots . .) \times\left(\frac{-21}{10} \times \frac{-5}{6}\right)$

(iv) $\frac{-12}{5} \times\left(\frac{4}{15} \times \frac{25}{-16}\right)=\left(\frac{-12}{5} \times \frac{4}{15}\right) \times(\ldots . .)$

Solution:

(i) $\frac{-23}{17} \times \frac{18}{35}=\frac{18}{35} \times \frac{-23}{17} \quad(\because a \times b=b \times a)$

(ii) $-38 \times \frac{-7}{9}=\frac{-7}{9} \times-38 \quad(\because a \times b=b \times a)$

(iii) $\left.\left(\frac{15}{7} \times \frac{-21}{10}\right) \times \frac{-5}{6}=\frac{15}{7} \times\left(\frac{-21}{10} \times \frac{-5}{6}\right) \quad[\because a \times(b \times c)=(a \times b) \times c)\right]$

(iv) $\frac{-12}{5} \times\left(\frac{4}{15} \times \frac{25}{-16}\right)=\left(\frac{-12}{5} \times \frac{4}{15}\right) \times \frac{25}{-16} \quad[\because a \times(b \times c)=(a \times b) \times c]$